Comparison of Combined Therapy (Curcumin + PRP) Versus Curcumin Alone PRP Alone in Terms of Quality of life Improvement in OSMF - Zeb, Muhammad Anwar; Tahir, Ramsha; Anis, Mehak; M. Arif, Lubna; Abid, Mustafa; Nadeem, Hera (Journal of Neonatal Surgery, 2025)
Oral Submucous Fibrosis (OSMF) is a chronic, progressive, and potentially malignant condition of the oral cavity that severely affects patients’ functional capacity and quality of life (QoL). This prospective, comparative, interventional study evaluated the therapeutic efficacy of combined Curcumin and Platelet-Rich Plasma (PRP) therapy versus Curcumin alone and PRP alone in improving QoL among OSMF patients. The study was conducted in the Department of Oral and Maxillofacial Surgery, Jinnah Hospital, Karachi, from January 2024 to January 2025, involving 90 clinically diagnosed OSMF patients randomized into three groups (n=30 each). Group A received Curcumin alone, Group B received PRP alone, and Group C received combined Curcumin + PRP therapy. Quality of life was assessed using the WHOQOL-BREF questionnaire, while clinical outcomes such as mouth opening and burning sensation were also recorded. Results demonstrated that the combined therapy group exhibited the greatest mean increase in mouth opening (9.4 ± 2.1 mm) and the most substantial reduction in burning sensation (VAS: 7.8 ± 1.2 to 1.3 ± 0.9), along with the highest WHOQOL-BREF score improvement (23.8 ± 5.6, p < 0.001). No major adverse effects were reported. The synergistic anti-inflammatory and regenerative effects of Curcumin and PRP were reflected in improved mucosal flexibility, pain reduction, and enhanced overall QoL. The findings suggest that the Curcumin + PRP combination offers a superior, safe, and biologically integrative therapeutic option for OSMF management..